Diluted magnetic semiconductor of p-type InMnP : Zn epilayer - Shon, Y; Jeon, HC; Park, YS; Lee, SJ; Kim, DY; Kim, HS; Kang, TW; Park, YJ; Yoon, CS; Kim, CK; Kim, EK; Kim, Y; et al. (ELSEVIER, 2005)
We investigated the characteristics of p-type InMnP:Zn epilayer using various measurements so as to compare its properties with those of bulk InMnP. InP:Zn epilayers of p-type were prepared by metal organic chemical vapor deposition and subsequently doped with Mn by heat treatment after the evaporation of Mn on top of InP:Zn epilayers using a molecular-beam epitaxy system. The samples were structurally characterized by X-ray diffraction. No evidence of secondary phase formation such as MnP, MnIn, and MnZn within the InMnP:Zn epilayer was found, and single-phase InMnP:Zn epilayer was well formed. The compositional results of energy dispersive X-ray peak displayed injected concentration of Mn near 1.5% and 3.0%. The results of photoluminescence measurement showed that optical broad transitions related to Mn appeared near 1.187, 1.198, and 1.227eV by the injection of Mn into the InP:Zn epilayer. Clear ferromagnetic hysteresis loops were observed at 10 K and the temperature-dependent magnetization of the samples with the Mn concentration near 1.5% showed ferromagnetic behavior persisting upto 390 and 300K and persisting upto 370K for the sample near 3.0%. It is found that in this system the proper annealing temperature is 450 degrees C. p-type InMnP:Zn epilayers represent a ferromagnet with superior properties (H-c = 311 G, saturation magnetization M = 7.6 x 10(-5) emu) in comparison with InMnP:Zn bulk (H-c = 134 G, M = 4.1 x 10(-5) emu) (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ROOM-TEMPERATURE; FERROMAGNETISM; MN